Using acute performance on a comprehensive neurocognitive, vestibular, and ocular motor assessment battery to predict recovery duration after sport-related concussions - Sufrinko, A. M.; Marchetti, G. F.; Cohen, P. E.; Elbin, R. J.; Re, V.; Kontos, A. P. (The American Journal of Sports Medicine, 2017)
Background: A sport-related concussion (SRC) is a heterogeneous injury that requires a multifaceted and comprehensive approach for diagnosis and management, including symptom reports, vestibular/ocular motor assessments, and neurocognitive testing. Purpose: To determine which acute (eg, within 7 days) vestibular, ocular motor, neurocognitive, and symptom impairments predict the duration of recovery after an SRC. Study Design: Cohort study (prognosis); Level of evidence, 2. Methods: Sixty-nine patients with a mean age of 15.3 ± 1.9 years completed a neurocognitive, vestibular/ocular motor, and symptom assessment within 7 days of a diagnosed concussion. Patients were grouped by recovery time: =14 days (n = 27, 39.1%), 15-29 days (n = 25, 36.2%), and 30-90 days (n = 17, 24.6%). Multinomial regression was used to identify the best subset of predictors associated with prolonged recovery relative to =14 days. Results: Acute visual motor speed and cognitive-migraine-fatigue symptoms were associated with an increased likelihood of recovery times of 30-90 days and 15-29 days relative to a recovery time of =14 days. A model with visual motor speed and cognitive-migraine-fatigue symptoms within the first 7 days of an SRC was 87% accurate at identifying patients with a recovery time of 30-90 days. Conclusion: The current study identified cognitive-migraine-fatigue symptoms and visual motor speed as the most robust predictors of protracted recovery after an SRC according to the Post-concussion Symptom Scale, Immediate Post-concussion Assessment and Cognitive Testing, and Vestibular/Ocular Motor Screening (VOMS). While VOMS components were sensitive in identifying a concussion, they were not robust predictors for recovery. Clinicians may consider particular patterns of performance on clinical measures when providing treatment recommendations and discussing anticipated recovery with patients.